Influential Parameters on Biomethane Generation in Anaerobic Wastewater Treatment Plants - Tabatabaei, Meisam; Sulaiman, Alawi; Nikbakht, Ali M.; Yusof, Norjan; Najafpour, Ghasem (IntechOpen, 2011)
None